Web-Based Employee Records Governance for Document Traceability and Verification in Plantation Workforce Administration Contexts - Natalia Fransiska Ginting; Ritna Wahyuni; Raden Aris Sugianto (Journal of Digital Technology and Computer Science, 2026)
Purpose – Employee data administration at PT. Barumun Raya Padang Langkat Binanga Estate has traditionally relied on manual procedures, creating difficulties in information retrieval, document management, verification, and administrative processing. This study aims to develop a web-based Employee Data Management Information System supporting structured, centralized, secure, and efficient personnel administration. Methods – The study employed a Research and Development approach using the Waterfall model, consisting of requirements analysis, system design, implementation, testing, and evaluation. Unified Modeling Language was used to model system processes and database interactions. The application was developed using PHP and MySQL, while functionality was evaluated through Black Box Testing. Findings – The resulting system integrates employee biodata, family information, supporting documents, verification workflows, reporting functions, and role-based access control in a centralized platform. Functional evaluation involved 15 testing scenarios covering authentication, employee data management, document handling, verification, reporting, and user access control. All tested functions produced outputs consistent with the specified requirements, indicating that the system operated correctly. The platform is expected to improve data organization, document control, verification accuracy, and administrative accessibility. Research Implications – The system is limited to employee data and document management and does not include payroll, attendance, recruitment, or performance appraisal modules. Evaluation was also restricted to functional testing. Future studies should therefore assess usability, performance efficiency, reliability, security, and user satisfaction through empirical testing. Originality – This study contributes an integrated personnel administration platform designed for plantation company operations, combining biodata, family records, supporting documents, verification mechanisms, reporting, and role-based access within a single web-based environment.